ROA DALAM MEMEDIASI FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Maulani, Mildatul; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The study aimed to determine ROA in mediating the factors that influence stock prices in mining companies listed on the IDX. In this study, the sampling technique used was purposive sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that the Current Ratio positively and significantly affects ROA. DER has a positive and significant effect on ROA. The current Ratio has a positive and significant effect on stock price; DER has a positive and significant effect on stock price; ROA has a negative and significant effect on stock price; the Current Ratio has a negative and insignificant effect on stock price through ROA, DER has a negative and insignificant effect on stock price through ROA.